MODERASI BERAGAMA DALAM BINGKAI KONSTITUSI NEGARA - Falentin Rambu Mbitu (Excelsis Deo: Jurnal Teologi, Misiologi, dan Pendidikan, 2021)
Conflicts between religious communities in Indonesia are not only experienced by the majority and minorities but also the majority with the majority. The purpose of the article answers the question: What is a State Constitution? How to Explore Historical, Sociological and Political Sources on the Constitution in State Life? How is religious moderation in the framework of the state constitution? The answers are: (1) The state constitution is a state government organization that has various forms and structural complexity, there is also a political or legal constitution but it also contains the meaning of an economic constitution. (2) The state constitutional institutions are: the People's Consultative Assembly (MPR), the People's Representative Council (DPR), the Regional Representatives Council (DPD), the President/Vice President, the Supreme Court, the Constitutional Court, the Judicial Commission, and the Supreme Audit. (3) Religious moderation is the frame of item 3 of the Pancasila “Unity of Indonesia”, in which President Joko Widodo to the Minister of Religion emphasizes the importance of the state (state constitution) implementing religious moderation because it strengthens national unity. Religious moderation can improve: national character, tolerance and national harmony, quality of education, and quality of leadership.Konflik masyarakat beragama di Indonesia bukan saja dialami oleh mayoritas dan minoritas tetapi mayoritas dengan mayoritas pun berlangsung. Tujuan artikel menjawab pertanyaan: Apa yang dimaksud dengan Konstitusi Negara?  Bagaimanakah Menggali Sumber Historis, Sosiologis dan Politik tentang Konstitusi dalam Kehidupan Bernegara?  Bagaimanakah moderasi beragama dalam bingkai konstitusi negara? Jawab adalah:  (1) Konstitusi negara adalah organisasi pemerintahan negara yang terdapat beragam bentuk dan kompleksitas strukturnya, terdapat pula konstitusi politik atau hukum akan tetapi mengandung pula arti konstitusi ekonomi.  (2) Lembaga konstitusi negara adalah:  Majelis Permusyawaratan Rakyat (MPR), Dewan Perwakilan Rakyat (DPR), Dewan Perwakilan Daerah (DPD),  Presiden/Wakil Presiden, Mahkamah Agung,  Mahkamah Konstitusi, Komisi Yudisial, dan   Pemeriksa Keuangan. (3) Moderasi beragama menjadi bingkai butir 3 Pancasila “Persatuan Indonesia”, di mana Presiden Joko Widodo hingga Menteria Agama, menegaskan betapa pentingnya negara  (konstitusi negara) melaksanakan moderasi beragama karena hal tersebut memperkuat persatuan bangsa. Moderasi beragama dapat meningkatkan: karakter bangsa, toleransi dan kerukunan bangsa, kualitas pendidikan, dan kualitas kepemimpinan.